Alice Walker - Gentry, Tony. (New York : Chelsea, 1993)
Examines the life and work of the author of "The Color Purple" and other works which focus on the lives of black women.
Includes bibliograhical references (p. 102) and index.
Keywords: Walker, Alice, -- 1944- -- Juvenile literature; Walker, Alice, -- 1944-; Authors, American -- 20th century -- Biography -- Juvenile literature; African American authors -- Biography -- Juvenile literature; Authors, American; African Americans -- Biography